Handbook of the media in Asia / edited by Shelton A. Gunaratne - "Gunaratne, Shelton A. (ed.)" (Delhi, 2000)
This comprehensive Handbook profiles the current state of the mass media in all the 25 countries/economies that comprise Asia. Following the customary division of the continent into South, Southeast and East, the 36 contributors provide a dispassionate and exhaustive discussion of the problems and issues relating to the media in each country/economy, covering not only the print and broadcasting industries but also the `new' media associated with the information technology revolution.
Keywords: "Mass media-Asia-Handbook, Manuals, etc"